Rationality, Faith and Human’s Everyday Living: A Philosophical Analysis on John Paul II’s Encyclical Letter of Fides et Ratio - Leuehaq, Timo Ata (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
Even though the problem of the relationship between faith and reason has been a very classical topic in the history of the discussion between philosophy and theology, the urgency of continuously re-discoursing on this topic remains. This article discusses the very topic based on John Paul II’s Encyclical Letter of Fides et Ratio with the argument that, although the emergency of that Letter is much more in the pastoral purposes for the establishment of the properness of the relationship of the two in Church’s ministry, this study finds that, from the philosophical perspective, this Letter implies some epistemological standpoints which one could think. Those ideas are the status of the two as the basic capacities of every human everyday searching for truth (and certainty) for living, the status of truth, certainty, and the completeness of human existence is the ultimate orientation of the epistemological operation of the two capacities, the status of everyday experiences as the basis or the foundation for thinking and some epistemological challenges and virtues which one has to (or might) consider and live by.